Floral biology, pollination behaviour and pollinators in bael (Aegle marmelos) in rainfed semi-arid conditions - A review (IASH Indian Journal of Arid Horticulture, 2025)
Bael a cross-pollinated fruit crop, relies heavily on effective pollinizers to enhance fruit set, yield, and quality, particularly in commercial cultivars and self-incompatible varieties. Pollinizers play a pivotal role in supporting reproductive success by providing abundant, viable, and compatible pollen that synchronizes with the flowering period of commercial varieties. This synchrony not only ensures successful pollination but also enables pollen storage for future use. The phenomenon of herkogamy further facilitates cross-pollination in bael, emphasizing the need for optimal pollinizer arrangements in orchards. Despite their importance, the role of pollinizers is often underestimated by fruit growers due to limited awareness and insufficient scientific information. This review consolidates existing knowledge on pollination biology, the ecological role of pollinizers, and the management practices required to optimize pollinator services in bael cultivation, particularly in rainfed semi-arid conditions. By addressing critical knowledge gaps, this study underscores the necessity of maintaining recommended pollinizer ratios and highlights strategies for enhancing pollination efficiency to achieve sustainable productivity in bael orchards.